DIFFERENTIAL REGULATION OF ANP AND BNP IN ACUTE DECOMPENSATED HEART FAILURE - DEFICIENCY OF ANP - Reginauld, Shawn H. (JACC Heart Fail, 2019)
BACKGROUND: The endocrine heart releases the cardiac hormones, atrial natriuretic peptide (ANP) and b-type natriuretic peptide (BNP) that play a key role in cardiovascular (CV), renal and metabolic homeostasis. In heart failure (HF), both plasma ANP and BNP are increased as a compensatory homeostatic response to myocardial overload. OBJECTIVES: We investigated the differential regulation of circulating ANP and BNP in acute decompensated heart failure (ADHF) patients and tested the hypothesis that a relative deficiency of ANP exists in a subgroup of ADHF patients. METHODS: We measured ANP and BNP in a small group of ADHF patients (n=112). To support our goal, we also prospectively recruited 129 healthy subjects to establish contemporary normal values for ANP and BNP. Plasma cGMP, ejection fraction (EF) and body mass index (BMI) were measured in these subjects. RESULTS: In ADHF, 74% of patients showed elevated ANP and BNP. Importantly, 26% of patients were characterized as having normal ANP (21% of this subgroup having normal ANP and elevated BNP). Cyclic GMP was lowest in the ADHF group with normal ANP (p<0.001), whereas BMI and EF were inversely related to ANP levels (p=0.003). CONCLUSIONS: Among a subgroup of patients hospitalized with ADHF, the presence of an ANP deficiency is consistent with a differential regulation of ANP and BNP and suggests the existence of a potentially compromised compensatory cardiac endocrine response. Our findings have implications in the pathophysiology, diagnostics and therapeutics of human HF.